Sargassum horneri inhibits fat accumulation via up-regulation of thermogenesis in obese mice - Min-Cheol Kang; Hyo Geun Lee; Sang Hoon Lee; Kyung-Mo Song; Hyun-Soo Kim; Sera Kim; Yun-Sang Choi; You-Jin Jeon (Journal of Functional Foods, 2022)
Obesity is a serious health problem worldwide and can lead to the development of metabolic syndromes, including hypertension, type 2 diabetes, and hyperglycemia. Therefore, we investigated the effect of an ethanol extract of Sargassum horneri (SH) on high-fat diet (HFD)-induced obese mice. To determine whether SH has an anti-obesity effect, C57BL/6 mice fed with HFD containing SH (100 and 300 mg/kg) were investigated for 7 weeks. The administration of SH significantly reduced body weight, white adipose tissue weight, fat accumulation in the liver, and white adipose tissues by increasing the mRNA expression of mitochondrial uncoupling protein 1 and mitochondrial uncoupling protein 3 in brown adipose tissues. Additionally, serum triglyceride, cholesterol, and leptin levels were significantly decreased in the mice administered SH compared with those of the HFD group. Our results showed that the ethanol extract of SH may be used as a functional food for treating obesity.